2017
DOI: 10.1364/josaa.34.000395
|View full text |Cite
|
Sign up to set email alerts
|

Scattering of electromagnetic waves from 3D multilayer random rough surfaces based on the second-order small perturbation method: energy conservation, reflectivity, and emissivity

Abstract: A theoretical investigation of energy conservation, reflectivity, and emissivity in the scattering of electromagnetic waves from 3D multilayer media with random rough interfaces using the second-order small perturbation method (SPM2) is presented. The approach is based on the extinction theorem and develops integral equations for surface fields in the spectral domain. Using the SPM2, we calculate the scattered and transmitted coherent fields and incoherent fields. Reflected and transmitted powers are then foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…Second and higher-order perturbative developments have also been investigated [9,[26][27][28][29]. It is worth highlighting that pertinent analytical developments following a boundary perturbation approach can be particularly cumbersome [27]; conversely, rigorous second-order volumetric-perturbative developments demand for an appropriate mathematical playground (the distribution theory for discontinuous test functions) [9].…”
Section: Perturbative Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Second and higher-order perturbative developments have also been investigated [9,[26][27][28][29]. It is worth highlighting that pertinent analytical developments following a boundary perturbation approach can be particularly cumbersome [27]; conversely, rigorous second-order volumetric-perturbative developments demand for an appropriate mathematical playground (the distribution theory for discontinuous test functions) [9].…”
Section: Perturbative Methodsmentioning
confidence: 99%
“…Notice that the first-order solution for the scattered field does not predict the cross-polarized intensity in the incidence plane. In [29] it has been demonstrated that there exists a "strong" condition of energy conservation in that the kernel functions multiplying the spectral density of each interface obey energy conservation exactly. Accordingly, the energy is conserved independent of the roughness spectral densities of the rough surfaces.…”
Section: Perturbative Methodsmentioning
confidence: 99%
“…The small perturbation method has been studied for random rough surface scattering extensively [1][2][3][4][5][6][7][8][9][10][11][12]. Recently, the method has been studied for multi-layered random rough surfaces [2,5,7] as an analytical method which has advantages over numerical methods for multiple rough interfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the method has been studied for multi-layered random rough surfaces [2,5,7] as an analytical method which has advantages over numerical methods for multiple rough interfaces. As the number of layers increases, numerical methods become costly in CPU and memory.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation